Ophthalmic manifestations in lyme borreliosis - Bergloeff, J... (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 1996)
Lyme Borreliosis is a multisystem disorder caused by the spirochete Borrelia burgdorferi. Although many ocular manifestations have been attributed to Lyme Borreliosis, they remain a rare clinical feature of the disease. The spirochetes invade the eye early and remain dormant, accouting for both early and late ocular manifestations which range from conjunctivis and keratitis to intraocular inflammatory syndromes and neuroophthalmic manifestations. Especially in endemic areas, ophthalmologists need to be aware of Borrelia burgdorferi as a possible causal agent. The aim of this article is to present a short review of ophthalmic disorders resulting from Borrelia burgdorferi infections.
Keywords: Diagnosis; Etiology; Eye infections, bacterial; Lyme disease